Microstructural aspect of pineal body: pinealocytes population - Gede Wirata; Putu Nia Calista Santoso; Putu Ayu Utami Dewantari (DiscoverSys Inc., 2018)
Background:Â Pineal tissue was compound with 2 types of cell known as pinealocytes and astrocyte cell. Furthermore, microanatomical research of pineal body is a rare procedure conducted for several years even in Indonesia, and its anatomical aspect needs to be explained. Â Aim: enrich the scope of knowledge related to mammalian pineal within the pineal body. Methods: 3 Wistar rats (Rattus novergicus), especially their pineal tissue, was extracted by pinealectomy method as a histotechnical procedure in a laboratory setting was prepared. Result: Pinealocytes characteristic are basophilic, large, regularly nucleus and a lot of mitochondria. On the other side, astrocyte has longer cytoplasmic processus found around the perivascular area and among the pinealocytes one. Conclusion: The quantities of pinealocytes appear as a most dominant cell that fills the inner part of the pineal body and probable to synchronize the production of melatonin and entirely supported by their neighbor, astrocyte cells.Â Keywords: histotechnical method, pinealectomy, epiphysis